Open Content Licensing from Theory to Practice - Guibault, Lucie (Amsterdam University Press, 2011)
Although open content licences only account for a fraction of all copyright licences currently in force in the copyright world, the mentality change initated by the open content movement is here to stay. To promote the use of open content licences, it is important to better understand the theoretical underpinnings of these licences, as well as to gain insight on the practical advantages and inconveniences of their use. This book assembles chapters written by renowned European scholars on a number of selected issues relating to open content licensing. It offers a comprehensive and objective study of the principles of open content from a European intellectual property law perspective and of their possible implementation in the areas of scientific publishing, of the re-use of government information, of the dissemination of works held by cultural heritage institutions and of the exercise of rights on music phonograms.